African bean production environments: their definition, characteristics and constraints - Wortmann, Charles S.; Allen, David J. (International Center for Tropical Agriculture, 1994)
Bean production in Africa is very heterogeneous with much variation in environmental conditions, cropping systems, preferences and constraints. This working document contains information on the many bean producing areas in Africa. The data were gleaned from numerous sources but a major part of these are from the observations of CIAT and national bean program researchers over the last ten years. Thirteen bean producing environments are defined from consideration of altitude, latitude, soil pH and seasonal rainfall. Seventy bean producing areas, having estimated annual bean production of between 2,000 and 220,000 hectares, are described on the bases of environmental and socio-economic characteristics, cropping systems, farmer and consumer preferences, and biotic and abiotic constraints. The importance of the constraints was evaluated both on a pan-African and a regional basis. Angular leaf spot, anthracnose, bean stem maggot, bruchids, low soil nitrogen and low soil phosphorus were determined to be the most important constraints to greater productivity on a pan-African basis.